THE EFFECT OF THE COMBINATION OF THE CONCENTRATION OF CASSAVA STARCH AND GLYCEROL MONOSTEARATE AS COATING MATERIAL ON CAVENDISH BANANA (Musa acuminata) STORAGE - Febrianty Mardhiyah, Wendy
Consumers want fruit purchased in fresh and appropriately ripe conditions, but fruit maturity is fruit to reach withering (senescence). Fruit with a high respiration rate is generally more perishable than fruit with slower respiration rate. Inhibition of respiration can be done by inhibiting the factors that influence it. Banana is a climacteric fruit with high respiration rate so that it has a short shelf life. Postharvest handling of bananas to extend their shelf life can be done by giving a coating layer. Some of the main components of the constituent layer consist of hydrocolloids and lipids. In this study, cassava starch was used as a polysaccharide hydrocolloid, GMS (Glycerol Monostearate) as a lipid component in the layer and potassium sorbate as an antifungal. The purpose of this study are to determine the effect of a combination formula of cassava starch-based coatings and GMS that is able to extend the shelf life of Cavendish bananas at a cool storage temperature (15 ± 2) oC and obtain the best combination formula of cassava-starch-based coatings and GMS that is able to extend the fruit shelf life Cavendish bananas at a cool storage temperature (15 ± 2) oC. Cavendish bananas used are bananas five days after given an ethylene (stage V). The testing parameters consist of organoleptic tests which contain colour, taste, aroma, hardness, and overall appearance; chemical characteristics contains of total dissolved solids, degree of acidity (pH) and respiration rate; physical characteristics which include weight loss and texture. The organoleptic test uses hedonic test parameters (preferences). Research design that used in this research is Completely Randomized Design which consists 16 treatments that are combination of cassava starch and GMS concentration in coating solution. The obtaining data would be analyzed with Analysis of Variance (ANOVA) at level 5%. If there was a difference in influence, that would be tested with Duncan’s Multiple Range Test (DMRT) at level 5% using IBM SPSS Statistic 21. The results showed that the bananas that were given a coating could last up to 9 days. Organoleptic, physical and chemical are the parameters but prioritize organoleptically. The results showed the combination of cassava starch and GMS as a coating material on Cavendish bananas gives a significant effect on organoleptic taste on day 3, organoleptic colour, overall appearance, weight loss, texture, total dissolved solids and degree of acidity until the 9th day. The coating did not give effect to aroma and firmness organoleptically. The best combination formula are the concentration of cassava starch 4% (w/v) and GMS 0.8% (w/w) and the concentration of cassava starch 4%(w/v) and GMS 0.9% (w/w).